P682 GO-CARE: a prospective multi-centre observational study of golimumab effectiveness and quality of life in a real life UC patient population in Italy. (25th January 2019) - Armuzzi, A; Gasbarrini, A; Marchi, S; Saibeni, S; Germano, V; Cercone, S; Bossa, F; Privitera, A C
Abstract: Background: The ultimate treatment target in UC must be the restoration of patient (PT) quality of life (QoL). 1 Aim of the study is to identify predictors of improvement QoL measured by Inflammatory Bowel Disease Questionnaire (IBDQ) after 8 and 56 weeks of treatment with Golimumab (GLM) and to investigate other effectiveness outcomes in a real life setting Methods: Responders to GLM induction therapy (by PMS) were enrolled 8 weeks after the start of GLM (wk8) and clinical-demographic data, present at start of GLM (baseline), were collected retrospectively. Predictors of IBDQ increase considered were: age, gender, weight, height, BMI, smoking status, comorbidities, disease duration/localisation, concurrent/previous therapy, CS dependence, FMS, PMS, endoscopic score, CRP and ESR. An interim analysis was conducted to evaluate (primary endpoint) predictors of IBDQ increase (≥16 points), achieved at wk8 and wk56 compared with baseline. Mean change in IBDQ at wk8, 32 and 56, clinical response (PMS decrease ≥2 points or ≥30% and decrease ≥1 point in rectal bleeding) and clinical remission (PMS ≤2 with no sub-score >1) at wk8, 32 and 56 [also per FMS] were also assessed (secondary endpoints). Results: 110 patients were enrolled. At baseline: mean age was 43years(69 males), mean disease duration was 9.5years, 77.3% of patients were steroid-dependent, 48.2% had pancolitis and 46.4% left-sided colitis. 80.9% of patients had moderate disease activity (median PMS 6) and 72.7% had a moderate endoscopic score (Mayo = 2), 20%, 12.7% and 77.3% of patients were treated with Corticosteroids, AZA, oral 5-ASA, mean IBDQ was 137. 27.3% of patients were anti-TNF experienced. By univariate analysis oral 5-ASA and higher disease activity (by PMS and FMS) were identified as predictors of QoL improvement at wk8 and wk32 respectively. From baseline( N = 110) to wk8 ( n = 110), 32 ( n = 67) and 56 ( n = 44): a significant increase of mean IBDQ( p < 0.05) (137, 170, 172, 178) and a significant reduction of median PMS( p < 0.0001) (6, 1, 0, 0) were observed. Median FMS significantly decreased from baseline ( N = 110) to wk56 ( N = 44) ( p < 0.001). Twenty-six and 12pts discontinued treatment before wk32 and wk56 respectively. At wk32: 59/93(63%) and 58/93(62%) were in sustained clinical response and remission. At wk56: sustained clinical response was observed in 44/82(53.3%) and 30/82(36.5%) and remission in 38/82(46.3%) and 23/82(28.0%) by PMS and FMS, respectively. Conclusions: This interim analysis of GO-CARE study identified the concomitant therapy with oral 5-ASA and higher disease activity as predictors of significant improvement of QoL. The analysis confirms the effectiveness of GLM in a real life setting with sustained response and remission, and improvement of QoL. Reference 1. L. Peyrin-Biroulet, et al . Am J Gastroenterol 2015; 110:1324–1338.